3 days of heat acclimation attenuates the monocyte HSP70 response following acute hypoxic exposure in humans - Lee, B.; Emery, E.; Hussain, A.; James, R.; Mackenzie, R.; Thake, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Research has shown that adaptation to one environmental stressor can induce protective characteristics for exposure to a second, new stressor. This occurs via activation of common protective pathways, such as the cytoprotective heat shock protein family (HSP70) and is termed cross acclimation (Horowitz et al., 2007). To date no research has investigated cross-acclimation responses between heat and hypoxia in whole body humans. Thus the aim of this study was to determine whether the initial phase of heat acclimation could confer increased cellular tolerance to an acute hypoxic exposure in humans. Method: 16 males were separated into two matched groups. Group A (mean ± SD; Age 21 ± 2.7yrs; height 1.85 ± 0.08m; mass 75.7 ± 8.2kg; PPO 289 ± 52 Watts; VO2peak; 46.15 ± 10ml/kg/min) completed 3 days of exercise heat acclimation; 60 minutes cycling at 50%VO2peak (Castle et al., 2011) in 40°C 20% RH. Group B (Age 20 ± 1.3yrs, height 1.75 ± 0.05m, mass 76 ± 10kg; PPO 284 ± 34 Watts; VO2peak 46.26 ± 8ml/kg/min) completed 3 days of exercise training in 20°C, 40%RH. Each group completed a hypoxic stress test (HST; 15 minutes rest, 60 minutes cycling at 50%VOpeak at 3000m above sea level) one week before, and 48 hours following the final day of acclimation. Venous blood samples were collected pre and post each HST and pre and post acclimation on days 1 and 3 for determination of intracellular monocyte HSP70 concentrations via flow cytometry. Results: There was no significant difference between group A and B in the percentage change from rest in HSP70 concentrations following the first HST (129 ± 59 Vs 130 ± 52%, p = 0.97). Heat acclimation produced a significant increase in basal HSP70 in group A (p = 0.03), with no change in group B (p = .218). The percent change in HSP70 from rest following the second HST was significantly lower in group A Vs group B (100.1 ± 13 Vs 133 ± 33%, p = 0.02). Discussion: The 3-day acclimation period induced a significant increase in basal HSP70 in group A, with no change in group B. The HSP70 response following HST2 was attenuated for group A, possibly indicating improved tolerance and ability to cope with the hypoxic insult via increased reserves of HSP70. This may be due to increased cytoprotection via pathways up-regulated by adaptation to heat stress, and shared by hypoxia. Work examining the shared pathways involved, and how improved cytoprotection impacts on whole body human performance is ongoing in our laboratory